Celestial lights : a novel - Pin, Cecile (Henry Holt and Company, 2026)
"A beautiful, heartbreaking novel about ambition, love, and space from the award-winning author of the Women's Prize longlisted Wandering Souls. January 28, 1986: Soon after launch, the Challenger shuttle falls out of the sky and into the sea. At the same time, Oliver Ines is born. Celestial Lights is his story. Ollie spends his childhood in an English village where his bedroom is covered in glow-in-the-dark wallpaper bearing the planets and stars. Decades later, he has become one of the most renowned astronauts of his time. When an enterprising billionaire taps him to lead a landmark mission to the distant moon Europa, Ollie makes a choice that will send his whole world spinning. As the mission advances deeper into unchartered territory, Ollie finds himself retreating into the past: his university days in London and years in the navy, relationships found and lost, becoming a husband and father. But will the world he remembers still be waiting for him when he returns? Cecile Pin's novel is a portrait of a complicated man whose unparalleled understanding of the universe doesn't always translate into stellar relationships on Earth. A breathtaking tale of memory, personal choices, and the relationships that define us, Celestial Lights is an unforgettable story of fate, love, and sacrifice that questions what we owe ourselves and our loved ones when our ambitions and loyalties collide"-- Provided by publisher.